Symbolism of Victorian Society in the Anthropomorphism of the Peter Rabbit Picture Book (1901) - Syahruni Junaid; Citra Andini (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This paper explores the anthropomorphic elements in Beatrix Potter's Peter Rabbit and their role in reflecting Victorian societal values. Through the depiction of Peter wearing human-like attire, notably his blue jacket, and standing upright, Potter imbues the character with human qualities, making him relatable to young readers. This anthropomorphism serves to symbolize both the innocence and adventurous spirit of childhood, while highlighting the tension between curiosity and the moral lessons of obedience and responsibility. The garden, as a space of both adventure and danger, mirrors the Victorian ideal of childhood exploration within the confines of authority. Peter's journey—marked by disobedience, mischief, and eventual growth—illustrates the duality of childhood: innocence coupled with the need for guidance. By balancing exploration with consequences, Potter’s narrative conveys timeless moral lessons, making Peter Rabbit a relatable, enduring story for both children and adults that transcends its Victorian context. The story’s appeal lies in its ability to speak to universal themes of personal growth and the balance between freedom and discipline. Potter’s use of anthropomorphism, coupled with her nuanced portrayal of childhood, ensures that Peter Rabbit remains an essential piece of literature that continues to resonate across generations.